COMPARISON BETWEEN LIQUID MEMBRANE AND POLYMER INCLUSION MEMBRANE FOR THE EFFECTIVE TRANSPORT OF SODIUM AND MAGNESIUM IONS (International Journal of Food and Nutritional Sciences, 2022)
The escalating demand for environmentally sustainable and cost-efficient methodologies forthe removal of toxic metal ions from contaminated aquatic environments and the retrieval ofvaluable noble metal ions from various waste matrices, often relegated to the status ofsecondary sources, has precipitated a surge in the exploration of techniques rooted in polymerinclusion membranes (PIMs).